Analisis Perencanaan dan Pengelolaan Sumber Daya Manusia dalam Usaha Ayam Penyet: Studi Kasus pada Ayam Penyet Buk Nur - Gladis Jelita; Hastiani Nasution; Zainarti Zainarti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the planning and management of human resources (HR) in the culinary business of Ayam Penyet, with a case study at Ayam Penyet Buk Nur. The research employs a qualitative method with a case study approach, collecting data through in-depth interviews, observation, and documentation. The findings indicate that thorough HR planning is crucial to ensure the availability of workforce that matches operational needs. Recruitment at Ayam Penyet Buk Nur is still informal, necessitating a competency-based selection system to acquire qualified employees. HR development through technical and work ethics training has proven to improve performance and service quality. A fair and transparent compensation system contributes to employee loyalty and retention. The internalization of Islamic business ethics strengthens a professional and harmonious work culture. Effective and adaptive HR management is key to the success and competitiveness of the Ayam Penyet business amid intense culinary market competition. The study recommends enhancing recruitment systems, continuous training, and the application of fairness and ethics principles in HR management to support business sustainability.